Pengaruh Pendapatan Asli Daerah, Pendapatan Transfer, dan Sisa Lebih Pembiayaan Anggaran terhadap Kinerja Keuangan Pemerintah Daerah (Studi Kasus pada Kabupaten/Kota di Provinsi Kepulauan Riau) - Mawardiati, Icha; Hasbi, Khairita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Local governments play a crucial role in national development through effective financial management. Under fiscal decentralization, regions independently manage financial resources but still face challenges in optimizing Local Own-Source Revenue (PAD) and managing transfer funds. The Riau Islands Province has experienced PAD fluctuations due to the COVID-19 pandemic and fiscal policies, despite maintaining positive economic growth. This study analyzes the financial performance of local governments in the Riau Islands using a quantitative descriptive method with secondary data from 2019 to 2024. Data analysis was conducted using SPSS 22.0 to examine the impact of PAD, transfer revenue (PT), and Budget Surplus (SiLPA) on regional financial performance. The findings indicate that PAD has a significant positive effect, PT has a positive but insignificant effect, and SiLPA has a negative but insignificant effect on financial performance. Simultaneously, all three variables have a significant impact. Optimizing PAD is the key to improving regional financial performance through enhanced taxation and the utilization of local economic potential. Additionally, improving the efficiency of PT and SiLPA management is essential to ensure optimal fund absorption for regional development.